Stragtegi Komunikasi Pariwisata Taman Air Mancur Sri Baduga Melalui Media Instagram @Urangpurwakarta - Sjaida, Gheya Madinatu; Khadijah, Ute Lies Siti; Novianti, Evie (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 02, Januari 2021DO - 10.24843/JUMPA.2021.v07.i02.p03, 2021)
Indonesian tourism was ranked 40th out of 140 countries in the world in the category of Travel and Tourism Competitiveness Index (TTCI) in 2019. This was of course supported by the advancement of regional tourism in Indonesia. One of the areas which is improving the tourism sector is Purwakarta Regency. Purwakarta Regency donates its favorite tourist destination, the Sri Baduga Situ Buleud Fountain Park which is the Top Five Tourism Destination in Indonesia. The media of his young people also helped to promote massive things related to the Sri Baduga Fountain Park. The media is named @urangpurwakarta. This research uses descriptive qualitative method with the concept of communication strategy. This research involved 3 key informants. The results of this research are the planning of @uranagpurwakarta in the form of determining targets, media and content, the implementation phase of @urangpurwakarta making Explore Purwakarta content, Purwakarta Original, Purwakarta Muda, and What the Facts Purwakarta. The evaluation phase of @urangpurwakarta becomes more active in providing information according to the direction of the organizer of Sri Baduga Water Park. Keywords: Communication Strategy, Tourism, Instagram, Purwakarta